2022
DOI: 10.1007/s13273-022-00320-3
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia extracts obtained by ultrasound-assisted extraction inhibit the inflammatory pathways

Abstract: Background Momordica charantia is a member of the Cucurbitaceae family and has traditionally been used for medical nutritional therapy to cure diabetes, and its various biological properties have been reported. However, several studies have demonstrated that M. charantia may exert toxic or adverse effects under different conditions. In this study, we prepared an M. charantia extract using ultrasound-assisted extraction, which is a green technology, and verified its anti-inflammatory effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…CCL5 and CCL17 are known to be increased under inflammatory responses; it is also known that an increase in inflammatory chemokines promotes IL-2 expression [46,47]. IL-2 is a critical pro-inflammatory factor because it promotes the expansion of T cells, the enhancement of natural killer (NK) cells, and the strengthening of the anti-tumor immune response [48]. In this study, we observed an up-regulation of inflammatory mediators, including IL-2; TNF-α, CCL5, and CCL17 mRNA expression; and iNOS and COX-2 protein expression in IL-6-treated Caco2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…CCL5 and CCL17 are known to be increased under inflammatory responses; it is also known that an increase in inflammatory chemokines promotes IL-2 expression [46,47]. IL-2 is a critical pro-inflammatory factor because it promotes the expansion of T cells, the enhancement of natural killer (NK) cells, and the strengthening of the anti-tumor immune response [48]. In this study, we observed an up-regulation of inflammatory mediators, including IL-2; TNF-α, CCL5, and CCL17 mRNA expression; and iNOS and COX-2 protein expression in IL-6-treated Caco2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Murine melanoma B16F10 and human embryonic kidney 293 T (HEK293T) cells were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA) and cultured as previously described (Kim et al 2022). In brief, the cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen, Carlsbad, CA, USA) with 10% heat-inactivated fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA, USA) and penicillin/streptomycin (100 U/mL) (Invitrogen, Carlsbad, CA, USA) at 37 °C under a humidified atmosphere containing 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…Whole-cell lysates of the cultured cells were obtained and separated using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and Western blot analysis was performed as described previously (Kim et al 2022). The primary and secondary antibodies used for the Western blot analyses were purchased from Cell Signaling Technology Inc. (Beverly, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%